High gain, low-profile, wideband archimedean spiral antenna with hexagonal fractal reflector surface - Sag, Rabia Nur; Tuylu, Tolgahan; Caliskan, Alper; Turker Tokan, Nurhan (YILDIZ TECHNICAL UNIV, 2025)
A tapered two-arm Archimedean spiral antenna with microstrip balun and fractal-based reflector surface is designed and manufactured. The operating impedance bandwidth of 1:13.3, and 3-dB AR bandwidth of 1:7 fulfills the requirement of high data rate, wideband and wide coverage zone. The antenna and balun are designed on FR-4 dielectric material with 1.6 mm thickness. The termination of the spiral arm is tapered to reduce the antenna size. To achieve a unidirectional radiation pattern, a reflector surface is used. The reflector surface is designed in a hexagonal fractal form in order to enhance the axial ratio and increase the antenna's gain. The radius and height of the reflector backed spiral antenna is 0.174 and 0.135 wavelengths at 150 MHz, respectively.
Keywords: Archimedean Spiral; Axial Ratio; Balun; Hexagonal Fractal; Wideband; Engineering